Development of the wiring diagram of the device based on the LoRa module RAK3172 - Makhanov, K.M.; Kurmanaliyev, N.B.; Musepov, S.B.; Naptalov, A.K.; Kenzhalieva, K.Z. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The paper presents the results of the development of circuitry of electronic device for the acquisition and transmission of telemetry data. The purpose of this work is to design and develop circuitry of the device for data acquisition using LoRa technology. The integrated end-to-end design environment Altium Designer was used to develop the electronic part of the device. The STM32F407VGT6 series microcontroller was used as the central control unit. A LoRa RAK3172 radio module is provided in the circuit for receiving and transmitting data. Unlike previous series, this module is equipped with a UART interface, which greatly simplifies the process of designing and writing a program for control. In this article the relevance of developing device with the use of LoRa-technology is considered. The theoretical basis of LoRa-modulation is briefly considered. The main section presents the results of the circuit design of the device, in particular, the inclusion diagram of the module and the control microcontroller. The information presented in the paper reflects only that part of the developed device, which is related to LoRa technology. In general, this work is part of a much larger project, which involves the use of GSM, Wi-Fi, RFID technology. Circuit of power supply is designed for 220 volt AC voltage with further transformation to +12V.
RAK3172 LoRa модулінің негізінде құрылғыны қосу схемасын əзірлеу
Разработка схемы подключения устройства на базе LoRa модуля RAK3172
Keywords: LoRa module; STM32 microcontroller; LFM modulation; electric circuit; modulation, gateway; design, circuitry; development; Altium Designer; radio channel